Benjamin Vaughan notes and remarks - Vaughan, Benjamin, 1751-1835.
Notes and remarks made on astronomers and astronomical observatories in the United States.
Physician, lawyer, merchant, agriculturist, and diplomat.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Astronomers -- United States; Astronomical observatories -- United States; Agriculturists; Diplomats; Lawyers; Merchants; Physicians